ANALISA PENERAPAN GOOD MANUFACTURING PRACTICE (GMP) PRODUK OLAHAN ROTI (STUDI KASUS: SAE ROTI KUNINGAN) - Kartika; cecep abdul cholik; Sandi Kurnia (Jurnal Fakultas Teknik Kuningan, 2024)
Good Manufacturing Practice (GMP) is a reference for every food processing industry so that it can pay attention to food safety so that it can produce quality and healthy food for consumption. This research aims to: (1) determine the implementation of the Good Manufacturing Practice (GMP) system at SAE ROTI. (2) Identifying errors and deviations in the implementation of Good Manufacturing Practice (GMP) at SAE ROTI. (3) Providing solutions and recommending improvements to errors in implementing Good Manufacturing Practice (GMP). This research was conducted using qualitative methods. Data collection in this research used observation and interviews. The analysis used is descriptive qualitative analysis. The resource persons in this research are Father Muhaemin and Mrs. Suheni as owners of the SAE ROTI industry. The collected data is processed and then analyzed. The results obtained from this research are the identification of the implementation of Good Manufacturing Practice (GMP) aspects at SAE ROTI that do not meet the GMP criteria and sanitation from the 12 GMP points has 1 point Good, 5 points Fair and 6 points Poor. Based on references from the Permenperin, in the 2 categories of major and critical deviations there are 5 major points and 6 critical points and recommendations for improvement are given based on the results of direct analysis.